The Influence of ESG Disclosures on Company Value In 5 ASEAN Countries - Muninggar, Aliya Inggita Prameswari; Pangestuti, Irene Rini Demi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research explores the impact of environmental, social, and governance (ESG) performance on company value in Indonesia, Malaysia, Thailand, Singapore, and the Philippines. The population of this research is manufacturing companies listed on the Stock Exchange and adopting the ESG system from 2018 to 2022. Purposive sampling was used to filter companies that meet the criteria of 65 companies. The findings of this research show that the overall ESG performance of manufacturing companies has a significant positive influence on company value in these five countries. Environmental performance and corporate governance do not affect company value. Meanwhile, social performance influences company value. In addition, environmental performance, social performance, and corporate governance together with control variables also influence firm value positively.